Model Pembelajaran Inovatif berbasis Deep learning untuk Meningkatkan Kualitas Praktik Profesional Guru - Shifa Aulia Salsabila; Nabila Azzahra; Ahmad Zainuri; Frika Fatimah Zahra (Lembaga Pengembangan Kinerja Dosen, 2026)
This reseach aims to analyze the role of an innovative deep learning-based instructional model in enhancing students’ conceptual understanding, critical thinking skills, and active engagement during classroom learning processes. The rapid development of educational technology currently demands continuous innovation in instructional practices, particularly to improve teacher quality and professionalism in addressing the challenges of the 21st century. To achieve this objective, this research employed a qualitative method with a literature review approach. Data were collected through a systematic review of various national journals, international journals, books, and relevant scholarly sources published within the last ten years. The findings indicate that the implementation of a deep learning-based instructional model can significantly enhance teachers’ creativity in designing instructional strategies, strengthen the effectiveness of the learning process, and improve the quality of teacher-student interaction. Furthermore, this approach encourages teachers to become more adaptive to digital technological advancements and more responsive to the diversity of students’ needs and learning styles. Therefore, the deep learning-based instructional model can serve as a strategic and sustainable solution for improving teachers’ professional practices in the modern education era.